The Presence of a Large Chiari Network in a Patient with Atrial Fibrillation and Stroke - Nneka Schwimmer-Okike; Johannes Niebuhr; Grit Gesine Ruth Schramek; Stefan Frantz; Heike Kielstein (Case Reports in Cardiology)
The Chiari network is an embryological remnant found in the right atrium, mostly without any significant pathophysiological consequences. However, several cardiac associations are reported in the literature including supraventricular tachyarrhythmias. We present a case of a 96-year-old body donor with a stroke episode and intermittent atrial fibrillations. The dissection of the heart revealed the presence of an immense Chiari network with a large central thrombus. The role of a Chiari network in the pathogenesis of stroke and pulmonary embolism is discussed.